2020
DOI: 10.1111/phn.12711
|View full text |Cite
|
Sign up to set email alerts
|

Education and employment outcomes in clients of the Nurse–Family Partnership

Abstract: Objectives Nurse–Family Partnership (NFP) is an evidence‐based home visitation program designed for low‐income, first‐time mothers to support pregnancy, child development, and maternal self‐sufficiency. This study examined educational and employment outcomes among NFP clients compared to a reference sample. Design Entropy balancing and a difference‐in‐difference design were used to compare the two samples of women from 2007 to 2016. Sample There were 127,427 women in the NFP sample, and 787 women in the refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…PHNs are better equipped to understand the needs and the goals of the organization when they have more information, which can improve work e ciency. This result supported the premise of the cognitive model of empowerment and accorded with studies that stated that employees with stronger self-e cacy would make more efforts to cope with the challenges of client outcomes and would feel more effective in their work (Piper, 2011;Royer, 2011;Flowers et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…PHNs are better equipped to understand the needs and the goals of the organization when they have more information, which can improve work e ciency. This result supported the premise of the cognitive model of empowerment and accorded with studies that stated that employees with stronger self-e cacy would make more efforts to cope with the challenges of client outcomes and would feel more effective in their work (Piper, 2011;Royer, 2011;Flowers et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…The CE results indicated that the PHNs believed that "The work that is performed is critical for health promotion" and "The work that is performed is crucial in promoting community health," and these beliefs were associated with psychological empowerment. Regarding organizational empowerment, the participants with a self-perception of "I can meet the work requirements and complete the work as scheduled" could also perceive that they were empowered in the workplace, which improved their work e ciency (Flowers et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The CE results indicated that the PHNs believed that "The work that is performed is critical for health promotion" and "The work that is performed is crucial in promoting community health", and these beliefs were associated with psychological empowerment. Regarding organizational empowerment, the participants with a self-perception of "I can meet the work requirements and complete the work as scheduled" could also perceive that they were empowered in the workplace, which improved their work efficiency [15]. Certain aspects of psychological empowerment, such as the sense of self-meaning of work, care management competence, and decision-making related participation, can be enhanced with related resources, such as more work-related information, specific suggestions for information, addressing problems, and positive encouragement, all of which can enable PHNs to be independent and to leverage all community resources to manage chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several long-term follow-up studies with a randomized controlled design (Kitzman et al, 2000; Olds et al, 2004, 2007) found statistically non-significant effects of the home visiting programs on mothers’ educational achievement, use of welfare benefits, and employment; however, the study by Olds et al (2002) found beneficial effects of home visiting on mothers’ employment. Finally, applying a quasi-experimental design, the evaluation of the Nurse Family Partnership program by Flowers, Sainer, Stoneburner, and Thorland (2020) found significant and positive effects on mothers’ educational and employment outcomes as compared to mothers in the control group. However, it must be noted that the authors considered these effects to be modest.…”
Section: Service Coordination Within Family Intervention Projectsmentioning
confidence: 98%